Evaluation of rotor blade models for rotor outwash - Rovere, F.; Morelli, U.; Steijl, R.; Barakos, G.N.; Vigevano, L. (My University, 2018)
In this work Computational Fluid Dynamics is used as a tool for rotor outwash evaluation. The paper concentrates on the validation of the method, presents different modelling approaches and concludes with suggestions on the use of the method for detailed simulations of rotor outwash. The required computer resources for the detailed computations of the wake are also discussed.